How to ride a dragon's storm - Cowell, Cressida (New York : Little, Brown, 2011)
Hiccup, the reluctant Viking hero, has three months, five days, and six hours to discover America, return to Berk, save his father, battle Polarserpents, and win the annual Inter-Tribal Friendly Swimming Race.
Originally published: London : Hodder Children's Books, c2008.
Accelerated Reader AR
Keywords: Vikings -- Fiction; Dragons -- Fiction; Humorous stories